Geoenvironmental and geophysical methods applied to identify natural attenuation process on a complex hydrogeological environment contaminated by hydrocarbons - Barbosa, Alexandre Muselli; Netto, Leonides Guireli [UNESP]; Guimarães, Camila Camolesi; Pereira, João Pedro Silva; Gandolfo, Otávio Coaracy Brasil; da Rocha Soares, Lelia Cristina; do Nascimento, Claudio Augusto Oller (Springer Nature, 2024)
Environmental contamination found in urban areas generally has a chemical composition that favors the generation of a variety of physical, chemical and biological processes that differ from natural soil parameters. Thus, understanding natural attenuation processes in tropical environments is still a challenge, as is understanding how biogeochemical processes can influence and modify natural soil characteristics. The study aimed to apply methods that are not commonly used in investigations of contaminated areas, in order to assess the applicability of non-invasive methodology for detailed stratigraphic characterization and biogeochemical changes resulting from contamination by hydrocarbons in a complex hydrogeological environment site. To date, few studies have presented results obtained using non-invasive techniques to understand biochemical processes. The research was based on the interpretation of results obtained by high-resolution physical environment characterization techniques (such as gamma geophysical profiling and electrical conductivity surveys) and chemical analysis of groundwater. The data was interpreted to obtain a detailed characterization of the study area and evidence of the occurrence of natural attenuation of creosote contamination. The results indicated that the combination of geoenvironmental and geophysical methods is an interesting alternative for obtaining data and understanding the mineralogical and stratigraphic variation of the contaminated area. The physical parameters variations obtained by the methods suggested the presence of local geochemical alterations resulting from natural processes of attenuation of contamination by aliphatic and aromatic hydrocarbons in a tropical environment. The natural attenuation processes were confirmed through groundwater samples, biological analysis and metagenomic classification.